Crystal Prediction and Design of Tunable Light Emission in BTB‐Based Metal‐Organic Frameworks. Issue 16 (12th June 2022) - Rimsza, Jessica M.; Henkelis, Susan E.; Rohwer, Lauren E. S.; Sava Gallis, Dorina F.; Nenoff, Tina M.
Abstract: Metal‐organic frameworks (MOFs) have recently been shown to exhibit unique mechanisms of luminescence based on charge transfer between structural units in the framework. These MOFs have the potential to be structural tuned for targeted emission with little or no metal participation. A computationally led, material design and synthesis methodology is presented here that elucidates the mechanisms of light emission in interpenetrated structures comprised of metal centers (M = In, Ga, InGa, InEu) and BTB (1, 3, 5‐Tris(4‐carboxyphenyl)benzene) linkers, forming unique luminescent M‐BTB MOF frameworks. Gas phase and periodic electronic structure calculations indicate that the intensity of the emission and the wavelength are overwhelmingly controlled by a combination of the number of interacting stacked linkers and their interatomic spacings, respectively. In the MOF, the ionic radii of the metal centers primarily control the expansion or shrinkage of the linker stacking distances. Experimentally, multiple M‐BTB‐based MOFs are synthesized and their photoluminescence was tested. Experiments validated the modeling by confirming that shifts in the crystal structure result in variations in light emission. Through this material design method, the mechanisms of tuning luminescence properties in interpenetrated M‐BTB MOFs have been identified and applied to the design of MOFs with specific wavelength emission based on their structure. Abstract : A material design framework is used to elucidate mechanisms of emission in interpenetrated metal‐organic frameworks (MOFs) structures. Computational modeling, validated by experiments, identifies that the emission intensity and wavelength are controlled by the number of stacked linkers and their spacings. Similar design frameworks can be used to design MOFs with specific wavelength emission based on their structure.